Loss of Gene Body Methylation in Eutrema salsugineum Is Associated with Reduced Gene Expression. (6th November 2018) - Muyle, Aline; Gaut, Brandon S
Abstract: Gene body methylation (gbM) is typically characterized by DNA methylation in the CG context within coding regions and is associated with constitutive genes that have moderate to high expression levels. A recent study discovered the loss of gbM in two plant species ( Eutrema salsugineum and Conringia planisiliqua ), illustrating that gbM is not necessary for survival and reproduction. The same paper stated there was no detectable effect of gbM loss on gene expression (GE). Here, we reanalyzed the GE data and accounted for experimental variability in expression level estimates. We show that the loss of gbM in E. salsugineum is associated with a small but highly significant decrease in GE relative to the closely related species Arabidospis thaliana. Our results are consistent with various evolutionary analyses that suggest gbM has a function, perhaps as a homeostatic effect on GE.